Legal aspects of Poland's participation in power politics of European Union - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2005)
After joining the European Union Poland became the participant of integrated power politics. Its basic task is to provide cheap and environment-friendly energy to customers. Three main purposes of power politics are: assurance of power safety, assurance of competitiveness on the market of manufacturers and distributors of energy, taking into account all the priorities of environmental protection, especially counteracting changes of climat. The structure of internal power market is carried out by harmonisation of national power markets. European Unions priority is creating a common power market which will be effective, safe and competitive. At the UE level two rules are accepted. The rule of controlled access - etitled receivers of electric energy have an access to net on the basis of tariffs accepted by the supervisors; these tariffs use not individually negotiated and they have aplication to all of entitled groups of electric energy receivers. The rule of negotiating the access - every user of the net negotiate with net operator the individual conditions of the access to the net in the area of delivery tariffs.